Consumers’ Innovativeness and acceptance determinants influence on fintech integration in Malaysian zakat institutions - Imran Mehboob Shaikh; Hanudin Amin; Mohamad Azmi Abdullah; Kamaruzaman Noordin (Lembaga Zakat Negeri Kedah, 2023)
Purpose ± This paper e[amineV Whe facWorV WhaW inflXence ZakaW pa\erV¶ acceptance towards FinTech integration using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Design/methodology/approach ± A survey was carried out and a purposive sampling method was used. Moreover, over 245 responses were gathered from individuals that are Zakat payers. Besides, the literature on the factors that influence an individual acceptance towards FinTech using the UTAUT model was also reviewed as an effort to contribute towards the factors that are significant in predicting the acceptance of FinTech services. Findings ± The results of the study revealed that consumer innovativeness and performance expectancy are the main factors in determining the acceptance of FinTech services. Moreover, social influence plays an important role in the acceptance of FinTech by Zakat payers. Research implications ± This study not only contributed to the theoretical extensions but also to practical implications, which would benefit the community of FinTech service providers in Malaysia. Limitations ± The limitations of this study were two but are not limited to, firstly, the respondents which were taken among Zakat payers in Malaysia, confining its contribution to the narrowed perspective of Sabah. Besides, this study also considers its contributions toward the use of the UTAUT in which the factors examined were specific which may elucidate that the generalization of the findings only includes FinTech, where the UTAUT comes into play. This study is an eye-opener for the merging perspective of both the UTAUT and FinTech in context of digital social finance using Fintech integration in Zakat institution in Sabah, Malaysia. Originality/value ± UTAUT is extended in the context of FinTech. Consumer innovativeness is incorporated in the context of the UTAUT model to be used in Zakat institutions integration with FinTech. Consumer innovativeness is yet to be tested and for that this study is a useful reference for academicians, policymakers, and future researchers.